Enhancement of Farm Income among the Marginal Farmers in West Bengal, India: Importance of Micro-Credit and Co-Operative Farming - Kundu, Amit; Goswami, Pubali (Asian Development Policy Review, 2022)
This paper, based on a field investigation in rural West Bengal, aims to identify possible ways which can enhance the farm income of marginal farmers. It is observed that the micro-credit system under a joint liability credit contract can play a dominant role during the time of disbursement of institutional farm credit, but the availability and size of this credit mainly depend on the operational holdings of the farm households. It is also observed that institutional credit, which is mainly provided through a micro-credit system, helps the beneficiary farmers to utilize their operational holdings optimally by enhancing their cropping intensity and or crop diversification. This creates a positive impact on their net farm income. It is also proved that the size of operational holdings creates a positive impact on the net farm income of the marginal farmer households at an increasing rate, which establishes the importance of cooperative farming through forming farmer’s groups at the ground level.